Inclusive Religion Education In Building Tolerance From School - Afifuddin Afifuddin; Ismail Hj. Ishak (Journal of Research and Multidisciplinary, 2020)
This article is an in-depth study of the importance of inclusive religion education and the involvement of teachers in schools in building attitudes and tolerance lives among students. Through the search for literature and reflection on contemporary issues, the author find that inclusive education is a form of education that allows students to open their vision to an increasingly broad horizon, able to cross ethnic group boundaries or cultural and religious traditions so that they can see "humanity" as a family have both differences and similarities in ideals. Religious teachers should lead students to understand religion as a "source of meaning", and not just an explanation of symbols and religious identity. In addition, school education should introduce the concept of tolerance which relies on the values of pluralism as an affirmative attitude towards religious and cultural pluralism